Barriers to glaucoma case finding as perceived by optometrists in Ireland. (17th July 2017) - Barrett, Catriona; O'Brien, Colm; Butler, John S; Loughman, James
Abstract : Background: This research was designed to provide an in‐depth exploration of the perceptions of optometrists relating to the challenges of glaucoma case finding in the Irish health‐care system. Methods: A survey was developed, piloted and distributed for anonymous completion by optometrists registered to practise in Ireland. The survey included 10 five‐level Likert items exploring potential barriers to glaucoma detection and a free‐text box for participants to comment more broadly. Results: One hundred and ninety‐nine optometrists (27 per cent of registrants) responded to the survey. Among the barriers identified, there was notable agreement (71 per cent) with the need for extra training on glaucoma detection. Logistic regression showed that optometrists without postgraduate qualifications were more likely to agree with the need for extra training (OR 3.2, 95 per cent CI 1.3–8.1). Respondents largely agreed (61 per cent) that patient unwillingness to pay additional fees for supplementary glaucoma‐specific tests was also a barrier. Appointment times of less than 30 minutes were significantly associated with six of the 10 proposed barriers to glaucoma detection. A logistic regression analysis (n = 179) confirmed that the time allotted per appointment was a significant predictor of the agreement time of optometrists as a barrier (χ 2 [1] = 13.52, p < 0.001). Multiple linear regression showed that optometrists with less experience, charging lower fees, and working in large multiples or franchised practices have the shortest appointment times. Conclusion: The strong link found between postgraduate education and the confidence of optometrists in detecting glaucoma indicates that optometrists wishing to increase their scope of practice in the new legislative environment in Ireland may more actively seek training in areas of interest. The responses also indicate a lack of funding for the level of diagnostic testing required for accurate glaucoma diagnosis. Recent increases in the state's eye examination fees look likely to address the identified time and financial barriers to glaucoma detection in Ireland. Future work should look to analyse the effects of increased funding on optometric case finding for glaucoma.